2008
DOI: 10.1177/1098300708319127
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of a Tier Two Behavior Intervention Based on Function of Problem Behavior

Abstract: The purpose of this study was to investigate the effectiveness of a tier two daily behavior card intervention and differential effects based on function of problem behavior. The participants were 36 elementary school students nominated for additional intervention beyond universal School-Wide Positive Behavior Support. Measures included standardized behavior rating scales and rate of office discipline referrals before and after 8 weeks of intervention. A multivariate analysis of variance was used, and results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 147 publications
(140 citation statements)
references
References 32 publications
5
134
0
1
Order By: Relevance
“…Teacher nomination was often described as an observed need. For example, McIntosh, Campbell, Carter, and Dickey (2009) stated participants were nominated by their classroom teachers based on "their levels of problem behavior and perceived need for support beyond universal Schoolwide Positive Behavior Support (lack of response to tier one intervention)" (p. 85). Regardless of how students were recruited for participation, they all exhibited persistent behavior problems (see Inclusion Criteria).…”
Section: Participants and Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Teacher nomination was often described as an observed need. For example, McIntosh, Campbell, Carter, and Dickey (2009) stated participants were nominated by their classroom teachers based on "their levels of problem behavior and perceived need for support beyond universal Schoolwide Positive Behavior Support (lack of response to tier one intervention)" (p. 85). Regardless of how students were recruited for participation, they all exhibited persistent behavior problems (see Inclusion Criteria).…”
Section: Participants and Settingmentioning
confidence: 99%
“…In one singlesubject study, a functional relation was discussed by authors who indicated one could not be established due to the limitation of the design (i.e., AB design; Swoszowski, Jolivette, & Fredrick, 2013). Statistically significant effects were reported for students' classroom behavior (e.g., Fabiano et al, 2010;Simonsen et al, 2011); daily report cards (e.g., Cheney et al, 2008;Cheney et al, 2009); scores on the Social Skills Rating System (Gresham & Elliott, 1990;e.g., Cheney et al, 2008;Cheney et al, 2009), Teacher Rating Form (Achenbach, 2001; e.g., Cheney et al, 2009), and Behavior Assessment Scale for Children 2 (Reynolds & Kamphaus, 2004;e.g., McIntosh et al, 2009); academic productivity and success (e.g., Fabiano et al, 2010); and office discipline referrals (e.g., Hawken, O'Neill, & MacLeod, 2011;McIntosh et al, 2009).…”
Section: Cico Variationsmentioning
confidence: 99%
“…This process required them to build consensus among faculty about what the appropriate behavior was, when a violation was dealt with in the classroom and when it was sent to the office. It also required the staff to agree on the use of a consequence system that was not one-size-fits-all but one that considers the function of the behavior (McIntosh, Kauffman, Carter, Dickey, & Horner, 2009). …”
Section: Establish Systems: Communication and Consensusmentioning
confidence: 99%
“…This tier serves 10-15% of the school population, the group decided that the tier two interventions should be easily implemented and require minimal assessment prior to implementation for students (McIntosh et al, 2009;Mitchell, Stormont, & Gage, 2011).…”
Section: The Planmentioning
confidence: 99%